Radiation/annealing-induced structural changes in GexAs₄₀-xS₆₀ glasses as revealed from high-energy synchrotron X-ray diffraction measurements - Kavetskyy, T.S.; Tsmots, V.M.; Stepanov, A.L. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Local atomic structure of GexAs₄₀-xS₆₀ glasses (x = 16, 24, 32, and 36) has
been investigated in the -irradiated (2.41 MGy dose) and annealed after irradiation
states by using the high-energy synchrotron X-ray diffraction technique. The
accumulated dose of 2.41 MGy is chosen to be close to the known in literature focal
point (~2.0 MGy) for the system tested, at which the y-irradiation-induced optical
(darkening) effect does not depend on the composition. It is established that the first
sharp diffraction peak (FSDP) is located at around 1.1 Е - in the structure factors S(Q) of
all the alloys studied. The FSDP position is found to be constant on radiation/annealing
treatment, but the intensity of the FSDP reveals changes under irradiation/annealing only
for the compositions with x = 16 and 24. The radiation/annealing-induced changes are
also observed on the pair distribution functions in the first and second coordination shells
for these compounds. Practically invisible effects on the FSDP and pair distribution
functions are found for the alloys with x = 32 and 36. The radiation/annealing-induced
structural changes detected mainly in the As - S sub-system of the glasses examined are
well explainable within the Tanaka approach for interpretation of the photo-induced
structural changes and related phenomena in As₂S₃ chalcogenide glass and similar
materials